2005
DOI: 10.1111/j.1365-2265.2005.02186.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring disease activity to predict therapeutic outcome in Graves’ ophthalmopathy

Abstract: SummaryObjective The concept of disease activity in Graves' ophthalmopathy (GO) might explain why as many as one-third of patients do not respond to immunosuppressive treatment, because only patients in the active stage of disease are expected to respond. The hypothesis was adopted that a parameter used to measure disease activity should be able to predict a response to immunosuppressive treatment. The aim of this study was to develop a multivariate prediction model in which all previous tested activity parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 32 publications
(61 reference statements)
1
36
0
10
Order By: Relevance
“…Disease duration is perhaps the most useful parameter for the differential diagnosis of these two particular subgroups of GO patients; as previously reported by Terwee and colleagues, GO duration >16 months was a significant predictor of no change and no response to therapy (27). A very recent study has shown that the increase of fibroadipose tissue is observed in untreated patients with a longer duration of disease (28), resulting in increasing proptosis and orbital fat volume mimicking disease progression.…”
Section: Chronic Congestive Gomentioning
confidence: 59%
“…Disease duration is perhaps the most useful parameter for the differential diagnosis of these two particular subgroups of GO patients; as previously reported by Terwee and colleagues, GO duration >16 months was a significant predictor of no change and no response to therapy (27). A very recent study has shown that the increase of fibroadipose tissue is observed in untreated patients with a longer duration of disease (28), resulting in increasing proptosis and orbital fat volume mimicking disease progression.…”
Section: Chronic Congestive Gomentioning
confidence: 59%
“…Thus, from this perspective, the population treated in the US trial had a lower likelihood of response to therapy. Another element that can predict response to therapy seems to be the duration of disease (24). Here again, the Italian trial recruited a population that had GO by an average of only 4.5 months by comparison with almost 3 times longer disease duration in the US trial.…”
Section: Analysis Of the Randomized Trials Characteristicsmentioning
confidence: 99%
“…As there is still no specific treatment available to date (Heufelder 1995), one can only try to avoid these sequelae by early administration of non-specific anti-inflammatory agents such as systemic corticosteroids or orbital ionizing irradiation. Although useful classifications for the assessment of disease activity have been introduced (Mourits et al 1989(Mourits et al , 1997Terwee et al 2005), it is yet not easy to clinically estimate the further course of inflammatory activity at a certain stage of disease. Thus, the purpose of our study is to find a technique that could not only detect but also quantify early inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%